PERGESERAN LAPANGAN USAHA SEKTOR PERTANIAN, PERTUBUHAN EKONOMI DAN PENURUNAN TINGKAT KEMISKINAN DI PROPINSI NUSA TENGGARA BARAT - IDA BAGUS EKA ARTIKA; A.A.MD. SURYA KENCANA; IDA AYU KETUT MARINI (Universitas Mahasaraswati Mataram, 2018)
The agricultural sector still contributes predominantly in economic activities in West Nusa Tenggara (NTB) province, although from year to year, there is a tendency to decrease its contribution to Gross Regional Domestic Product, but in absolute value its production keep increasing. Economic growth of NTB Province also tends to increase from year to year above the national economic growth rate, has implications for the success in reducing the percentage of poor people in NTB. This study is a literature review of the variables of the decreasing role of agriculture sector and the rate of economic growth, to the reduction of poverty level in the province of NTB period 2011 to 2017. Data collection method is the method of documentation of secondary data, with descriptive discussion and simple statistical analysis of linear regression multiple and coefficient of determination. The results of the study found that the shift in the contribution of the agricultural sector to non-agricultural sectors positively affected the decline in poverty, and on the other hand economic growth negatively affected or opposed to the decline of poverty, which means that the higher the economic growth, the more poverty will decline. From the results of this study, it is suggested that the agricultural sector will continue to be developed by intensifying the intensification program, and non-agricultural sectors still have the potential to be developed optimally. The increase in the contribution of sectors outside agriculture, especially those contributing below 5% should be increased, can still be optimized. The mining sector is a fluctuating business field, given that the mining and quarrying sectors are ultimately processed overseas so as to contribute to the economic performance of NTB Province, so that sectors outside mining and quarrying should be prioritized for development in the future